2001
DOI: 10.1152/ajpheart.2001.280.2.h925
|View full text |Cite
|
Sign up to set email alerts
|

Potent vasodilator responses to human urotensin-II in human pulmonary and abdominal resistance arteries

Abstract: The peptide human urotensin-II (hUT-II) and its receptor have recently been cloned. The vascular function of this peptide in humans, however, has yet to be determined. Vasoconstrictor and vasodilator responses to hUT-II were investigated in human small muscular pulmonary arteries [approximately 70 microm internal diameter (ID)] and human abdominal resistance arteries (approximately 200 microm ID). Vasodilator responses were investigated in endothelin-1 (3 nM) precontracted vessels and, in the small pulmonary v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
114
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(116 citation statements)
references
References 12 publications
1
114
0
1
Order By: Relevance
“…The response is limited to large elastic vessels and does not include small resistance vessels. On the other side, UII can also promote vasodilation via an endothelium-dependent nitric oxide (NO)-mediated response (Bottrill et al 2000, Stirrat et al 2001. It is difficult to describe the effects of UII in vivo as they have not been conserved during evolution.…”
Section: Uts2r5mentioning
confidence: 99%
“…The response is limited to large elastic vessels and does not include small resistance vessels. On the other side, UII can also promote vasodilation via an endothelium-dependent nitric oxide (NO)-mediated response (Bottrill et al 2000, Stirrat et al 2001. It is difficult to describe the effects of UII in vivo as they have not been conserved during evolution.…”
Section: Uts2r5mentioning
confidence: 99%
“…19,20 In previous studies in this population we found that UTN is inversely, rather than directly, related to CV stress hormones like norepinephrine and neuropeptide Y 20 and to the endogenous inhibitor of NO synthesis, asymmetrical dimethylarginine (ADMA). 21 UTN is a potent NOdependent vasodilator in pulmonary and mesenteric circulation in humans, 22 and we hypothesized that these links may …”
mentioning
confidence: 99%
“…19,20 In previous studies in this population we found that UTN is inversely, rather than directly, related to CV stress hormones like norepinephrine and neuropeptide Y 20 and to the endogenous inhibitor of NO synthesis, asymmetrical dimethylarginine (ADMA). 21 UTN is a potent NOdependent vasodilator in pulmonary and mesenteric circulation in humans, 22 and we hypothesized that these links may serve to mitigate the high risk associated with sympathetic overactivity and NO inhibition in ESRD. 23 This hypothesis was corroborated by cognate observations showing that high plasma UTN predicts better clinical outcomes, ie, reduced CV complications in ESRD 23 and longer survival in patients with stage 3 to 4 chronic kidney disease.…”
mentioning
confidence: 99%
“…3 There are important species differences in the reactivity of different vessels to UTN. For example, UTN vasoconstricts monkey vessels, vasodilates human pulmonary vasculature and mesenteric resistance vessels, 4 and has no effect on human subcutaneous resistance vessels. 5 UTN also causes vascular smooth muscle hypertrophy.…”
mentioning
confidence: 99%